2016
DOI: 10.1186/s12884-016-0938-4
|View full text |Cite
|
Sign up to set email alerts
|

Dirty and 40 days in the wilderness: Eliciting childbirth and postnatal cultural practices and beliefs in Nepal

Abstract: BackgroundPregnancy and childbirth are socio-cultural events that carry varying meanings across different societies and cultures. These are often translated into social expectations of what a particular society expects women to do (or not to do) during pregnancy, birth and/or the postnatal period. This paper reports a study exploring beliefs around childbirth in Nepal, a low-income country with a largely Hindu population. The paper then sets these findings in the context of the wider global literature around i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 50 publications
1
69
1
3
Order By: Relevance
“…54,72 In Hinduism, postpartum women are not allowed to leave their home until the 11th day, which is a special day for rituals and the naming of newborns, so, for some women in remote areas, this ritual practice means they do not attend for PNC. 79 Among Muslims seeking behaviour related to pregnancy and childbirth was poor, 31 and other local minority religions (Kirat Mundhum and Christians) had high home delivery rates. 31,46 Education The educational level of women had synergistic impacts on improving their status within households and communities, leading them to be more aware of their health and more informed about where to go when in need of health services.…”
Section: Wealth Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…54,72 In Hinduism, postpartum women are not allowed to leave their home until the 11th day, which is a special day for rituals and the naming of newborns, so, for some women in remote areas, this ritual practice means they do not attend for PNC. 79 Among Muslims seeking behaviour related to pregnancy and childbirth was poor, 31 and other local minority religions (Kirat Mundhum and Christians) had high home delivery rates. 31,46 Education The educational level of women had synergistic impacts on improving their status within households and communities, leading them to be more aware of their health and more informed about where to go when in need of health services.…”
Section: Wealth Statusmentioning
confidence: 99%
“…Such beliefs include considering childbirth as dirty and untouchable, and not allowing postpartum women to eat certain food items such as green vegetables or meat, due to the perceived belief that such food can cause puerperal sepsis. 42,56,60,74,79 Some cultural practices may lead to delayed care in case of complications, 77 which unintentionally put women at risk. 34 Psychosocial factors Psychosocial support, networks and social stress were identified as influencing factors for use and non-use of maternity services.…”
Section: Materials Circumstancesmentioning
confidence: 99%
“…9 Sharma et al from Nepal also reported that, the cultural practices, taboos and beliefs during pregnancy and around childbirth found in Nepal largely resonate with those reported across the globe. 10 Even few practices are harmful to mother and baby. It is particularly more important in developing countries like India where the birth rates are high.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, placenta burial is a symbolic representation that the placenta and the land are sources of nurturing for the baby (Abel et al 2001). The Nepalese also value the placenta burial ritual as it could affect the health of the new-born for his or her entire life if not buried or placed somewhere in the proper way (Sharma et al 2016). Participants in this study reported the burial of the placenta and umbilical cord in the house for the fear of witchcraft, which may be practiced on the placenta to bring harm to the child.…”
Section: T H E P L a C E N T A A N D T H E C H I L D 'S F I R S T H Amentioning
confidence: 99%
“…Other important beliefs practiced during the postpartum period (such as breastfeeding beliefs, placenta ritual, and naming rituals) are rarely addressed in postpartum studies conducted in traditional societies. The exception is a qualitative study conducted in Nepal that explores infant-related post-natal cultural practices, such as placenta rituals, naming, and weaning ceremonies (Sharma et al 2016).…”
Section: Introductionmentioning
confidence: 99%